Anti-Diabetic Potential of Sargassum horneri and Ulva australis Extracts In Vitro and In Vivo - Young-Hyeon Lee; Hye-Ran Kim; Min-Ho Yeo; Sung-Chun Kim; Ho-Bong Hyun; Young-Min Ham; Yong-Hwan Jung; Hye-Sook Kim; Kyung-Soo Chang (Current Issues in Molecular Biology, 2023)
Sargassum horneri (SH) and Ulva australis (UA) are marine waste resources that cause environmental and economic problems when entering or multiplying the coastal waters of Jeju Island. We analyzed their anti-diabetic efficacy to assess their reusability as functional additives. The alpha-glucosidase inhibitory activity of SH and UA extracts was confirmed, and the effect of UA extract was higher than that of SH. After the induction of insulin-resistant HepG2 cells, the effects of the two marine extracts on oxidative stress, intracellular glucose uptake, and glycogen content were compared to the positive control, metformin. Treatment of insulin-resistant HepG2 cells with SH and UA resulted in a concentration-dependent decrease in oxidative stress and increased intracellular glucose uptake and glycogen content. Moreover, SH and UA treatment upregulated the expression of IRS-1, AKT, and GLUT4, which are suppressed in insulin resistance, to a similar degree to metformin, and suppressed the expression of FoxO1, PEPCK involved in gluconeogenesis, and GSK-3β involved in glycogen metabolism. The oral administration of these extracts to rats with streptozotocin-induced diabetes led to a higher weight gain than that in the diabetic group. Insulin resistance and oral glucose tolerance are alleviated by the regulation of blood glucose. Thus, the SH and UA extracts may be used in the development of therapeutic agents or supplements to improve insulin resistance.